Legal guide on drawing up international contracts for the construction of industrial works (UN New YorkUS, 1988)
Seeks to assist parties in negotiating and drawing up international contracts for the construction of industrial works by identifying the legal issues involved in these contracts, discussing possible approaches to the solution of the issues, and where appropriate, suggesting solutions which the parties may wish to incorporate in the their contract.
DC